Eficiência do uso da água em cultivo da alface com diferentes doses de biomassa de cobertura com e sem restrição hídrica - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Vegetables, especially lettuce, are those that require the most water in their production, and need attention in relation to water deficit. The objective of this work was to evaluate the efficiency of water use due to the addition of cover crop phytomass with and without water restriction in lettuce cultivation, in Juruti-Pará. The study was conducted from August to October 2023 in the CJUR/UFOPA greenhouse, in Juruti, PA. The treatments consisted of a 3x2 factorial, where there were three different phytomass coverages of the Brachiaria spp crop, being: 0 Mg ha-1 (control), 5 Mg ha-1 and 10 Mg ha-1 , and two types of water restriction (with restriction and without restriction), with 4 replications, in a completely randomized design. A soil with known fertility was used as substrate for the cultivation of lettuce. Transplanting took place in August 2023. The parameters evaluated were: plant height, number of leaves, root length, shoot and root dry mass, leaf diameter. The first period of water restriction occurred on the 15th day after transplanting and was extended for 10 days. The second restriction took place at 30 DAT, and lasted three days. Water use efficiency was determined by the relationship between water consumption and plant dry mass. The results were subjected to homogeneity of variance and normality tests, and analysis of variance. Comparison of treatments for qualitative factors was performed using the Tukey test at 5% probability. Water use efficiency was higher in treatments with phytomass coverage of 5Mg/ha-1 . Treatments without water restriction showed the best development for the parameters evaluated for lettuce cultivation.
Keywords: Déficit hídrico; Lactuca sativa; Panicum spp; CNPQ:: CIÊNCIAS AGRÁRIAS